Utility of cholangioscopy in patients with surgically altered anatomy after percutaneous transhepatic biliary drainage - Dalal, Ankit; Kamat, Nagesh; Patil, Gaurav; Vadgaonkar, Amol; Parekh, Sanil; Vora, Sehajad; Maydeo, Amit (Endoscopy International Open, 2025)
Surgical therapy that alters the biliary anatomy makes endoscopic access to the biliary system difficult. These surgeries promote cholestasis, calculi development and lead to biliary stricture. Stricture resolution and removal of intrahepatic bile duct stones remain challenging.This was a retrospective analysis of prospective data from patients with altered surgical anatomy with intrahepatic bile duct stones/strictures. Percutaneous transhepatic biliary drainage (PTBD) was attempted, followed by transhepatic SpyGlass cholangioscopy for stricture or removal of intrahepatic bile duct stones. The number of sessions, stricture dilatation, and complications were noted. A cholangiogram revealing a clear duct was a technical success, and stricture resolution was considered a clinical success. Complete ductal clearance was clinical success in those with stones. Patients with follow-up of a minimum of 6 months were included.Twenty-four patients, 16 of whom were male (66.7%), median age 41.5 years (interquartile range [IQR] 38.2–49) successfully underwent PTBD. The most common indication was biliary stricture in 13 (54.2%), followed by intrahepatic stones in six (25%) and stones with strictures in five patients (20.8%). Most patients had undergone Roux-en-Y hepaticojejunostomy (22; 91.7%), and the level of bile duct obstruction was hilum in 20 (83.3%). The median (IQR) total bilirubin levels reduced from 6.6 (5.1–8.3) to 1.8 mg/dL (1.2–2.8) after PTBD; P <0.001. The technical success was 90.9% after a median (IQR) number of two (1.7–2) SpyGlass sessions; clinical success was 88.9% after a median of three (3–4) SpyGlass sessions. Abdominal pain (8.3%) and cholangitis (12.5%) were the complications after cholangioscopy. The median (IQR) follow-up duration was 7 months (6–8).SpyGlass cholangioscopy, although challenging, is a safe option for intrahepatic stones and strictures with excellent short-term outcomes and minimal complications.
Keywords: Pancreatobiliary (ERCP/PTCD); Cholangioscopy; PTCD/PTCS